Literature Review: The Antimicrobial Potential of Xanthorrhizoland and Curcuminoids from the Rhizomes of Curcuma Xanthorrhiza (Temulawak) - Habibah, Habibah; Mierza, Vriezka (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Antimicrobial resistance is a global threat that drives the search for new antimicrobial agents derived from natural sources. Temulawak (Curcuma xanthorrhiza) contains two major active compounds, xanthorrhizol and curcuminoid, known for their antimicrobial properties. This review aims to analyze and compare the antimicrobial potential of these compounds to determine the most prospective candidate for development as an active natural antimicrobial agent in Indonesia. A systematic literature review was conducted using the PRISMA guideline on articles published between 2015 and 2025, obtained from Google Scholar and PubMed. Of the 251 articles identified, 10 met the inclusion criteria and were analyzed. The results indicate that xanthorrhizol exhibits stronger and broader antimicrobial activity, with a Minimum Inhibitory Concentration (MIC) of 16 µg/mL, inhibition zones of 12–14 mm, and inhibition rates exceeding 90% against Candida albicans and Enterococcus faecalis. In contrast, curcuminoid shows variable activity (inhibition zones of 0–16 mm) and its effectiveness increases after photodynamic activation (Photodynamic Therapy, PDT) through the formation of Reactive Oxygen Species (ROS). In conclusion, xanthorrhizol is more promising as a primary natural antimicrobial agent, while curcuminoid serves as a complementary compound to enhance antimicrobial effectiveness.